BLOCKCHAIN AS A SECURE AND DECENTRALIZED COMMUNICATION TOOL FOR FUTURE SUSTAINABLE DEVELOPMENT - Shahzool Hazimin, Azizam; Syarilla Iryani, A. Saany; Yousef A. Baker, El-Ebiary (2020)
This article presents a distributed ledger (blockchain) technology in terms of future sustainable development. This study based on private, public and global communication in different industries. Growing demands of secure and decentralized transactions throughout the world show the need for Blockchain technology as a means of operations and communications. The blockchain system is entirely decentralized and allows users to exchange messages effectively and securely. The paper's highlight is the projected future use of blockchains as a communication tool in every business and digital economy for secure and sustainable development, showcasing its benefits and limitations that are confirmed based on the experts' different experiments. Furthermore, the article offers recommendations for using the blockchain to complicate its identification in future communications significantly. Paper also concludes that using the blockchain system can be beneficial and strengthen communication and digital technologies in the future.